A glade in the kelp forest: socio-spatial opportunities for multi-trophic aquaculture Hout Bay, South Africa - Van Der Wat, Nelia (School of Architecture, Planning and Geomatics, 2024)
This thesis is centred around the ideas of multi-trophic aquaculture (two or more aquatic species are cultivated and harvested from the same area), with a specific focus on implementing a kelp aquaculture framework. Kelp is an ecosystem driver, filter feeder and a versatile product. In South Africa, kelp forests are present along the West Coast due to the upwelling of the Benguela system in which cold, nutrient-rich waters from the Antarctic flow into the Atlantic Ocean. These kelp forests are all in a prolific and stable state, with little-to-no threat. The abundance and under-exploitation of kelp has labelled it as a low-value marine resource, under the Marine Living Resources Act of 1998. Under the same Act mentioned above, quotas of fishing rights have been distributed between the commercial, small-scale and subsistence fisheries. Criticism of this legislation is that it does not actually acknowledge the latter, and commercial fisheries receive disproportionately more quotas than those of small-scale operations. As a result, poaching of high-value marine resources in South Africa has steadily increased over the years. This thesis aims to promote multi-trophic aquaculture as a framework for environmental justice and appropriate resource management of lowvalue marine resources for subsistence and small-scale fisheries. Hout Bay harbour was selected as the case study area because a large proportion of the Hout Bay harbour and surrounds is abandoned and has fallen into disrepair, causing an economic decline in the area. This has greatly impacted the marginalised community of Hangberg who live behind the harbour, and greatly rely on it for jobs, opportunities and food. The West Battery and on the southern boundary of the harbour adjacent to Hangberg was selected as a site for intervention. The site is eroded, neglected and provides little amenity and ecosystem service. Kelp aquaculture was used as an entry point into the project, and the project has evolved from this into a multi-trophic intervention that targets biodiversity and environmental justice concerns. A sensitive approach will be undertaken to conceptualise the programmatic, ecological and spatial qualities of this aquaculture intervention. The result will be a dynamic, sustainable, democratic, productive and delightful landscape intervention that will benefit visitors, small-scale fishing economies and the proliferation of the kelp forest itself.